Expression of Endothelin-1, Endothelin Receptor-A, and Endothelin Receptor-B in facial melasma compared to adjacent skin - da Silva CN; Miot HA; Grassi TF; Dias-Melício LA; Santos L; Espósito ACC (Dove Medical Press, 2023)
Carolina Nunhez da Silva,1 Hélio Amante Miot,1 Tony Fernando Grassi,2 Luciane Alarcão Dias-Melício,2- 4 Leandro Santos,2,3 Ana Cláudia Cavalcante Espósito1 1Department of Dermatology, São Paulo State University (UNESP) - Medical School of Botucatu, Botucatu, São Paulo State, Brazil; 2UNIPEX - Experimental Research Unit, São Paulo State University (UNESP) - Medical School of Botucatu, Botucatu, São Paulo State, Brazil; 3Laboratory of Immunopathology and Infectious Agents - LIAI, São Paulo State University (UNESP) - Medical School of Botucatu, Botucatu, São Paulo State, Brazil; 4Department of Pathology, São Paulo State University (UNESP) - Medical School of Botucatu, Botucatu, São Paulo State, BrazilCorrespondence: Ana Cláudia Cavalcante Espósito, Division of Dermatology and Radiotherapy, São Paulo State University (UNESP) - Medical School of Botucatu, Botucatu, São Paulo State, Brazil, Email anaclaudiaesposito@gmail.comBackground/Objectives: Although melasma is highly prevalent, its pathogenesis is not yet fully understood. In the skin, endothelin-1 (ET-1) is primarily produced by keratinocytes in response to UVB exposure, which is mediated by an increase in IL-1α or reactive oxygen species. ET-1 plays a role in melanogenesis by binding to specific receptor B (ERB) or receptor A (ERA). However, the expression of ET-1, ERA, and ERB in melasma has not been systematically investigated. The objective of this study was to evaluate the expression of ET-1, ERA, and ERB in facial melasma compared to the adjacent unaffected skin.Methods: Cross-sectional study, with 40 skin samples (20: facial melasma; 20: adjacent unaffected skin) from women with facial melasma without treatment for 30 days except for sunscreen. A triple staining immunofluorescence technique was performed for anti-vimentin, DAPI, plus one of the following antibodies: (a) anti-ET1, (b) anti-ERA; (c) anti-ERB. Interfollicular areas on the slides of each topography (melasma; unaffected skin) were photographed in triplicate under confocal laser microscopy. The mean staining intensities of the image histograms (0- 255 pixels intensity) were estimated for different types of cells (suprabasal keratinocytes, basal layer, and upper dermis) and were blindly compared between topographies.Results: The mean (SD) age of the participants was 44.9 (9.2). The expression of ET-1 was increased in the whole epidermis with melasma when compared to the adjacent skin, being 32.8% (CI95% 14.7%- 52.6%) higher in the spinous layer (p=0.013), 30.4% (CI95% 13.7%- 47.9%) higher in the basal layer (p=0.014), and 29.7% (CI95% 11.4%- 49.7%) higher in the melanocytes (p=0.006). There was no noticeable expression of ET-1 within the cells on the upper dermis. Neither ERA nor ERB resulted in differential epidermal expression between melasma and unaffected skin (p≥ 0.1).Conclusion: ET-1 is expressed more intensely on the epidermis from the skin with facial melasma compared to the unaffected adjacent skin.Keywords: melasma, immunofluorescence technique, endothelin-1, endothelin receptor-A, endothelin receptor-B